The Body Economic : Life, Death, and Sensation in Political Economy and the Victorian Novel - Gallagher, Catherine (Book collections on Project MUSE., 2006)
The Body Economic revises the intellectual history of nineteenth-century Britain by demonstrating that political economists and the writers who often presented themselves as their literary antagonists actually held most of their basic social assumptions in common. Catherine Gallagher demonstrates that political economists and their Romantic and early-Victorian critics jointly relocated the idea of value from the realm of transcendent spirituality to that of organic ""life, "" making human sensations--especially pleasure and pain--the sources and signs of that value. Classical political econom